2006
DOI: 10.1108/02651330610646296
|View full text |Cite
|
Sign up to set email alerts
|

Foreign diversification vs concentration strategies and firm performance

Abstract: Purpose -The purpose of this study is to examine the impact on firm performance of foreign concentration vs diversification strategies, as well as the moderating role played by market, product and firm characteristics. Design/methodology/approach -Moderated regression analysis is used. Findings -Distribution and cultural distance (CU) moderate the relationship between foreign concentration-diversification and stock market performance; while the non-repetitive character of product purchase moderates the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 51 publications
1
15
0
1
Order By: Relevance
“…Though the foreign‐expansion strategy is a determinant of XP, empirical studies that have tested this relationship have confirmed what is questionable about the options considered (L. E. Brouthers & Nakos, ; Katsikea et al, ;Lee & Yang, ; Mas et al, ; Ruzo et al, ). A firm's export‐market expansion strategy may be considered a determining factor of its XP, but there is neither theoretical nor empirical consensus as to which type of strategy results in a better XP (Lee & Yang, ).…”
Section: Theory and Hypothesesmentioning
confidence: 97%
See 2 more Smart Citations
“…Though the foreign‐expansion strategy is a determinant of XP, empirical studies that have tested this relationship have confirmed what is questionable about the options considered (L. E. Brouthers & Nakos, ; Katsikea et al, ;Lee & Yang, ; Mas et al, ; Ruzo et al, ). A firm's export‐market expansion strategy may be considered a determining factor of its XP, but there is neither theoretical nor empirical consensus as to which type of strategy results in a better XP (Lee & Yang, ).…”
Section: Theory and Hypothesesmentioning
confidence: 97%
“…Depending on the number of markets where a firm is looking to establish its presence, two alternative strategies have been identified and discussed: concentration and diversification (e.g., Ayal & Zif, ; Lee & Yang, ; Losada, Ruzo, Barreiro, & Navarro, ; Mas, Nicolau, & Ruiz, ), which are also referred to as concentration and dispersion/spreading (e.g., Crick, Chaudhry, & Bastone, ; Katsikea, Theodosiou, Morgan, & Papavassiliou, ; Katsikeas & Leonidou, ; Piercy, ).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its strength, event study has been well accepted and widely employed in a variety of disciplines (Agrawal & Kamakura, 1995). Examples of the event study application on management include market expansion strategy (Mas, Nicolau, & Ruiz, 2006), celebrity endorsements (Agrawal & Kamakura, 1995), strategic alliances (Kalaignanam, Shankar, & Varadarajan, 2007), IT investments (Meng & Lee, 2007), electronic commerce announcement (Subramani & Walden, 2001;Dewan & Ren, 2007) and Internet channel additions (Geyskens et al, 2002). To elaborate, Lin, Jang, and Chen (2007) apply the event study methodology to assess the market value of e-service initiatives.…”
Section: Event Studymentioning
confidence: 99%
“…However, as there are other sequential forms of exporting without necessarily obey this linearity, the innovation-related models have a limited explanatory power (Andersen, 1993). There are different types of international starters with different background, knowledge about international operations and sources of information that aim other exporting patterns apart of the evolutionary pattern (Kuivalainen et al, 2012;Kuivalainen et al, 2007;Mas et al, 2006). Besides considering internal decisions and changes in the organizational structure, managers have to consider the organizational context, as there are variables such as government incentives, the economic integration, the possibility of participating in international networks and the request of the company's products and services by unknown foreign customers that influence the internationalization process (Crick & Chaudhry, 1997).…”
Section: The Innovation-related Modelsmentioning
confidence: 99%